A 12-Week Assessment of the Treatment of White Spot Lesions with CPP-ACP Paste and/or Fluoride Varnish. (11th October 2016) - Güçlü, Zeynep Aslı; Alaçam, Alev; Coleman, Nichola Jayne
Abstract : This 12-week clinical study evaluated the impact of 10% CPP-ACP and 5% sodium fluoride varnish regimes on the regression of nonorthodontic white spot lesions (WSLs). The study included 21 children with 101 WSLs who were randomised into four treatment regimes: weekly clinical applications of fluoride varnish for the first month (FV); twice daily self-applications of CPP-ACP paste (CPP-ACP); weekly applications of fluoride varnish for the first month and twice daily self-applications of CPP-ACP paste (CPP-ACP-FV); and no intervention (control). All groups undertook a standard oral hygiene protocol and weekly consultation. Visual appraisals and laser fluorescence (LF) measurements were made in weeks one and twelve. The majority of WSLs in the control and FV groups exhibited no shift in appearance, whereas, in the CPP-ACP and CPP-ACP-FV groups, the lesions predominantly regressed. The visual and LF assessments indicated that the extent of remineralisation afforded by the treatments was of the following order: control ~ FV < CPP-ACP ~ CPP-ACP-FV. Self-applications of CPP-ACP paste as an adjunct to standard oral hygiene significantly improved the appearance and remineralisation of WSLs. No advantage was observed for the use of fluoride varnish as a supplement to either the standard or CPP-ACP-enhanced oral hygiene regimes.